Saul Bellow as a Humorist with Special Reference to ‘Humboldt’s Gift’ - Sinha, Arti (Journal of Advanced Research in Journalism & Mass Communication, 2019)
Saul Bellow was the Nobel Prize-winning American novelist. His chief novels include, ‘The Adventures of Augie March’, ‘Herzog’, ‘Humboldt’s Gift’ and most recently, ‘Ravelstein’. He is known for having captured the vitality of the American street and the hybrid energies of the immigrant-experiences in America; he did so in prose inimitable density and power. His influence on American fiction is nearly as reflective as boisterous as his prose. His novels seem to be posing the question of how you can be an intellectual and still live in this world. If in his Mr. ‘Sammler’s Planet’ there is not a clear answer, in ‘Humboldt’s Gift’, there seems to be: one can survive this world with humour and compassion. I think, there is so much of the martyr in Saul Bellow, due perhaps to his Jewish background, that in order to make his reading more palatable for the average reader, he needed to ameliorate his martyr complex with a lot of humour. His ‘Humboldt’s Gift’ is its fine example. How to cite this article: Sinha A. Saul Bellow as a humorist with special reference to ‘Humboldt’s Gift’. J Adv Res Jrnl Mass Comm 2019; 6(4): 36-39. DOI: https://doi.org/10.24321/2395.3810.201912